Instagram sebagai Cyber Public Relation di Era 4.0 - Marlina Rahmi; Fajar Muharam; TUTY MUTIAH MUTIAH (Jurnal Public Relations (J-PR), 2021)
Management communicating easily and efficiently using cyber public relations. Corporate management in the industrial era 4.0 by exploring potential with a digitalization system. The current social media platform is Instagram which is often used as cyber public relations. The researcher cyber public relations social media industry era 4.0 in the activities of the KT&G Sangsang Univ Indonesia program using Instagram with industrial corporate cyber public relations in the 4.0 era. The research was conducted on the activities of the KT&G Sangsang Univ Indonesia program with qualitative research methods with descriptive analysis and the research subjects were informants through in-depth interviews in providing the required data. The findings in this study are that Instagram's cyber public relations social media can be useful for public relations. Corporate management can communicate with a broad target audience through social media Instagram.